Petal-shaped Co-Mg-Al-LDH as well as preparation method and application thereof
Through the method of controlling the dual-responsive ionic liquid microemulsion system, petal-shaped Co-Mg-Al-LDH with a high specific surface area was prepared, which solved the problems of agglomeration and small specific surface area when preparing Co-Mg-Al-LDH in the traditional co-precipitation method, and achieved efficient catalytic degradation of ciprofloxacin.
Patent Information
- Application Number
- CN202510057750.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-08
AI Technical Summary
Traditional co-precipitation methods are prone to problems of agglomeration and small specific surface area when preparing Co-Mg-Al-LDH, resulting in low antibiotic degradation efficiency in water.
The synthesis of petal-shaped Co-Mg-Al-LDH was regulated by a dual-responsive ionic liquid microemulsion system. Through hydrothermal reaction and microstructure control of the microemulsion, petal-shaped Co-Mg-Al-LDH nanoparticles with high specific surface area and stability were prepared.
The efficient catalytic degradation of ciprofloxacin by petal-shaped Co-Mg-Al-LDH in the aqueous environment is achieved, reducing environmental pollution and cost in the production process, and improving the efficiency of antibiotic degradation.
Smart Images

Figure CN119771415A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of environmental functional materials and organic pollution control, and specifically relates to a petal-shaped Co-Mg-Al-LDH and a preparation method and application thereof. Background Art
[0002] In the history of the development of medicine, the discovery of antibiotics is undoubtedly a major breakthrough. Since the widespread use of penicillin, many new antibiotics have been introduced, which have played a key role in the prevention and treatment of bacterial diseases. In many fields such as medical care and agricultural breeding, the role of antibiotics is crucial, especially the second-generation fluoroquinolone antibiotics, such as ciprofloxacin (CIP), which has been used significantly more frequently during the COVID-19 pandemic. However, as a type of antibiotic, CIP has an increasingly serious residual problem in the water environment due to its low absorption rate and abuse in pharmaceutical and personal care products. Generally, the discharge of antibiotics mainly comes from wastewater from the medical and pharmaceutical industries, which contains a large amount of disinfection by-products such as phosphorus, nitrogen, and chlorine, which makes traditional wastewater treatment methods unsatisfactory in terms of cost and effect. Therefore, the development of an efficient and environmentally friendly new technology to remove antibiotics from water bodies has become a hot topic in academic research.
[0003] Persulfate advanced oxidation processes (PS-AOPs) are a technology that activates persulfate (PMS) to produce a variety of active substances and then degrade various pollutants. This technology has shown high efficiency in the degradation of antibiotics. The key to PS-AOPs is to use different catalysts to activate persulfate, thereby generating a variety of active substances including sulfate radicals to achieve the degradation of organic pollutants. Despite this, the activation efficiency of persulfate under standard environmental conditions is not high, which limits its application potential in the field of environmental remediation. Layered double hydroxides (LDHs) have shown broad application prospects in many fields such as pollutant adsorption, medicine and organic catalysis due to their special layered structure, adjustable chemical composition, excellent chemical stability and memory effect. In particular, cobalt magnesium aluminum-based LDH (Co-Mg-Al-LDH) is considered to be an effective material for activating persulfate due to its high stability, good reusability and environmental friendliness in the process of antibiotic degradation, which can promote the efficient catalytic degradation of antibiotics. However, the traditional coprecipitation method often encounters problems of agglomeration and low specific surface area when preparing Co-Mg-Al-LDH. Therefore, developing new preparation technologies to optimize the microstructure of Co-Mg-Al-LDH and improve the degradation efficiency of antibiotics in water has become a research hotspot.
[0004] Dual-responsive ionic liquid microemulsion technology plays an increasingly important role in the preparation of nanomaterials due to its unique nano-sized dispersion system. Since it is composed of surfactants, ionic liquids and aqueous or organic phases, the system formed has the characteristics of thermodynamically stable isotropy, providing an ideal microenvironment for the synthesis of nanomaterials. Nanomaterials prepared by dual-responsive ionic liquid microemulsion technology have the advantages of uniform particle size and controllable size, and are widely used in the preparation of catalysts, semiconductors, superconductors and magnetic materials.
[0005] In the technical route of Co-Mg-Al-LDH catalytic degradation of antibiotics in water, an ionic liquid microemulsion system with dual response characteristics is first used to regulate the synthesis of Co-Mg-Al-LDH. Then, the prepared Co-Mg-Al-LDH is combined with PMS, and wastewater containing antibiotics is put into the water treatment facility to quickly achieve the degradation of antibiotics with the help of catalysis. This technology not only shows excellent performance at the laboratory level, but also shows the possibility of expansion to industrial applications due to its high efficiency, economy and ease of operation. Therefore, Co-Mg-Al-LDH synthesized by dual-responsive ionic liquid microemulsion system, as an emerging catalytic material, shows obvious superiority in activating PMS and catalyzing the degradation of antibiotics, providing innovative solutions and technical support for addressing the current problem of antibiotic pollution in water environments. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a petal-shaped Co-Mg-Al-LDH and a preparation method and application thereof in view of the deficiencies of the above-mentioned prior art. The present invention uses a dual-responsive ionic liquid microemulsion system to regulate the synthesis of petal-shaped Co-Mg-Al-LDH. The preparation method of the present invention solves the technical problems of easy agglomeration, small specific surface area, and difficulty in treating antibiotic-containing medical wastewater in the traditional coprecipitation method. The dual-responsive ionic liquid microemulsion is used as a microscopic reaction container to effectively control the nucleation and growth process of petal-shaped Co-Mg-Al-LDH nanoparticles. The catalytic performance of petal-shaped Co-Mg-Al-LDH in degrading CIP in an aqueous environment is verified by detailed characterization of its crystal phase, structure, chemical composition and morphological characteristics.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing petal-shaped Co-Mg-Al-LDH, the preparation method comprising the following steps:
[0008] S1, mixing polar phase water, non-polar phase ionic liquid and surfactant uniformly to obtain a dual-responsive ionic liquid microemulsion;
[0009] S2, first adding a cobalt source to the dual-responsive ionic liquid microemulsion obtained in S1 to obtain a mixed solution, and then sequentially adding a magnesium source, an aluminum source and a precipitant to the mixed solution to obtain a mixture; subjecting the mixture to a hydrothermal reaction to obtain a primary product;
[0010] S3. The primary product obtained in S2 is washed and then dried to obtain a petal-shaped Co-Mg-Al-LDH.
[0011] Preferably, the mass ratio of the polar phase water, the non-polar phase ionic liquid and the surfactant in S1 is 3.715:1.5:0.75.
[0012] Preferably, the surfactant is polyethylene glycol octylphenyl ether, and the non-polar ionic liquid is [C 10 mim][Ttfa]or[C 10 mim][Btfa].
[0013] Preferably, the preparation method of the non-polar phase ionic liquid is:
[0014] S101, firstly mixing N-methylimidazole and bromodecane, then adding ethyl acetate and mixing evenly, and then refluxing under N2 protection to obtain a crude product; washing the crude product with ethyl acetate a, then evaporating, and then drying to obtain an ionic liquid 1-decyl-3-methylimidazole bromide;
[0015] S102, dissolving the ionic liquid 1-decyl-3-methylimidazolium bromide obtained in S101 in ethanol to obtain [C 10 mim]Br ethanol solution; the [C 10 mim]Br ethanol solution was added to an anion exchange column to obtain [C 10 mim]OH;
[0016] S103, the [C 10 mim]OH and benzoyltrifluoroacetone were mixed evenly, reacted at room temperature for 24 hours, and then evaporated to obtain a crude product a; the crude product a was dried to obtain [C 10 mim][Btfa];
[0017] S104, the [C 10 mim]OH and 2-thenoyltrifluoroacetone were mixed evenly, reacted at room temperature for 24 hours, and then evaporated to obtain a crude product b; the crude product b was dried to obtain [C 10 mim][Ttfa].
[0018] Preferably, in S101, the molar ratio of the N-methylimidazole to the bromodecane is 1:1, and the volume ratio of the ethyl acetate to the total amount of the N-methylimidazole and the bromodecane is 1:2; the reflux temperature is 80°C and the time is 72h; the crude product is washed with ethyl acetate a 3-5 times; the evaporation temperature is 50-60°C and the time is 30-60min; the drying temperature is 60°C and the time is 2 days; and the volume ratio of the ionic liquid 1-decyl-3-methylimidazole bromide to the ethanol in S102 is 9:1.
[0019] Preferably, in S103, [C 10 mim]OH and the molar ratio of the benzoyltrifluoroacetone is 1:1, and the [C 10 mim]OH and the molar ratio of the 2-thenoyltrifluoroacetone is 1:1; the drying temperature in S103 and the drying temperature in S104 are both 50°C, and the time is both 2 days; the evaporation temperature in S103 and the evaporation temperature in S104 are both 50-60°C, and the time is both 30-60 min.
[0020] Preferably, the cobalt source in S2 is cobalt nitrate hexahydrate, the magnesium source is magnesium nitrate hexahydrate, the aluminum source is aluminum nitrate nonahydrate, and the precipitant is urea; the molar ratio of the cobalt element in the cobalt source, the magnesium element in the magnesium source, the aluminum element in the aluminum source and the precipitant is 1:50:(16-17):(291-292); the concentration of the cobalt element in the cobalt source in the mixed solution is 0.6-0.7 mmol·mL -1 .
[0021] Preferably, the temperature of the hydrothermal reaction in S2 is 140° C. and the time is 24 h; the primary product in S3 is washed 3-5 times with anhydrous ethanol, and the drying temperature is 60° C. and the time is 4 h.
[0022] The present invention also provides a petal-shaped Co-Mg-Al-LDH, which is prepared by the above-mentioned method for preparing the petal-shaped Co-Mg-Al-LDH.
[0023] The invention also discloses use of the petal-shaped Co-Mg-Al-LDH for degrading ciprofloxacin in water.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention limits the precursor cobalt source, magnesium source, aluminum source and precipitant to the inside of the tiny water droplets of the dual-responsive microemulsion through a microemulsion-hydrothermal method, limits the nucleation and growth of petal-shaped Co-Mg-Al-LDH, regulates the microstructure of Co-Mg-Al-LDH, and prepares petal-shaped Co-Mg-Al-LDH. The reaction does not use organic solvents and alkaline solutions, which reduces pollution to the environment. Moreover, the preparation process of the present invention has simple steps and common equipment, which reduces the cost and risk factor in the production process. At the same time, the preparation method of the present invention is simple in process, easy to operate, and mild in conditions. The prepared petal-shaped Co-Mg-Al-LDH composite material has a strong catalytic degradation ability for antibiotics in water, can be used for the removal of CIP in wastewater, and has broad application prospects.
[0026] 2. The present invention uses a dual-responsive ionic liquid microemulsion as a microreactor to not only limit the nucleation and growth of petal-shaped Co-Mg-Al-LDH nanomaterials. At the same time, the size, distribution and composition of the petal-shaped Co-Mg-Al-LDH nanoparticles are also controlled to obtain a petal-shaped Co-Mg-Al-LDH with high efficiency in degrading antibiotics in water. The physical phase and structure, component composition and morphological characteristics of the petal-shaped Co-Mg-Al-LDH are characterized, and applied to the degradation of high-concentration antibiotics in wastewater to obtain a catalyst material that is simple to operate, inexpensive, and can efficiently degrade antibiotics.
[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 [C] prepared in Example 1 of the present invention 10 Phase diagram of mim][Ttfa] / H2O / TX-100 ionic liquid microemulsion.
[0029] Figure 2 This is the XPS graph of the petal-shaped Co-Mg-Al-LDH prepared in Example 1 of the present invention.
[0030] Figure 3 This is a SEM image of the petal-shaped Co-Mg-Al-LDH prepared in Example 1 of the present invention.
[0031] Figure 4 This is a N2 adsorption-desorption characterization diagram of the petal-shaped Co-Mg-Al-LDH prepared in Example 1 of the present invention.
[0032] Figure 5 This is a graph showing the change in CIP adsorption removal rate when Co-Mg-Al-LDH of different masses prepared in the present invention is catalyzed by 0.05 g of PMS.
[0033] Figure 6 The figure is a graph showing the degradation rate variation of CIP catalytic degradation when 0.01 g of Co-Mg-Al-LDH prepared in the present invention is catalyzed by different amounts of PMS.
[0034] Figure 7 This is a N2 adsorption and desorption characterization diagram of Co-Mg-Al-LDH prepared in Comparative Example 1 of the present invention.
[0035] Figure 8 This is a SEM image of the Co-Mg-Al-LDH prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a petal-shaped Co-Mg-Al-LDH, which comprises the following steps:
[0039] S1, the mass ratio of polar phase water (H2O), [C 10 mim][Ttfa] and polyethylene glycol octylphenyl ether (TX-100) were mixed evenly to obtain a dual-responsive ionic liquid microemulsion;
[0040] The [C 10 The preparation method of mim][Ttfa] is:
[0041] S101, first add N-methylimidazole and bromodecane in a molar ratio of 1:1 into a 250 mL round-bottom flask, then add ethyl acetate as a solvent and mix well, then reflux for 72 h at 80° C. under N2 protection to obtain a crude product; wash the crude product with ethyl acetate a 4 times, then evaporate the ethyl acetate a using a rotary evaporator at 55° C. for 50 min, then dry in a vacuum drying oven at 60° C. for 2 days to obtain an ionic liquid 1-decyl-3-methylimidazole bromide ([C 10 mim]Br); the volume ratio of the total amount of the ethyl acetate to the N-methylimidazole and the bromodecane is 1:2;
[0042] S102, dissolving the ionic liquid 1-decyl-3-methylimidazolium bromide obtained in S101 and ethanol in a volume ratio of 9:1 to obtain [C 10 mim]Br ethanol solution; the [C 10 mim]Br ethanol solution was added to the anion exchange column to perform Br - Exchange, get [C 10 mim]OH; the acid-base titration method was used to determine the [C 10 mim]OH ethanol solution [C 10 mim]OH concentration;
[0043] S103, the [C 10 mim]OH and 2-thenoyltrifluoroacetone (Ttfa) were mixed uniformly at a molar ratio of 1:1, reacted at room temperature (25°C) for 24 hours, and then evaporated by rotary evaporation at 55°C for 50 minutes to evaporate water to obtain a crude product a; the crude product a was placed in a vacuum drying oven and dried at 50°C for 2 days to obtain [C 10 mim][Ttfa], the [C 10 mim][Ttfa] has an anion of 2-thenoyltrifluoroacetone and a cation of 1-decyl-3-methylimidazole;
[0044] S2. Firstly, cobalt nitrate hexahydrate is added to the dual-responsive ionic liquid microemulsion obtained in S1 to obtain a mixed solution; magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea are added to the mixed solution in sequence, and the mixture is stirred at room temperature (25° C.) for 0.5 h to obtain a mixture; the mixture is subjected to a hydrothermal reaction at a temperature of 140° C. for 24 h to obtain a primary product;
[0045] The concentration of cobalt element in the cobalt nitrate hexahydrate in the mixed solution is 0.7 mmol·mL -1 ; The molar ratio of the cobalt element in the cobalt nitrate hexahydrate, the magnesium element in the magnesium nitrate hexahydrate, the aluminum element in the aluminum nitrate nonahydrate and the urea is 1:50:16.5:291.5;
[0046] S3. The primary product obtained in S2 was washed with anhydrous ethanol four times, and then placed in a vacuum drying oven at 60° C. for 4 hours to remove the residual solvent (anhydrous ethanol) to obtain a petal-shaped Co-Mg-Al-LDH.
[0047] Comparative Example 1
[0048] This comparative example provides a method for preparing Co-Mg-Al-LDH by a conventional coprecipitation method, the method comprising the following steps:
[0049] S1. 0.175 g of cobalt nitrate hexahydrate, 0.1025 g of magnesium nitrate hexahydrate and 0.075 g of aluminum nitrate nonahydrate were mixed, and a sodium hydroxide solution was added to control the pH value to be maintained between 10 and 12, and the mixture was stirred at room temperature (25° C.) for 0.5 h to obtain a mixture; the mixture was subjected to a hydrothermal reaction at a temperature of 140° C. for 24 h to obtain a primary product;
[0050] S2. The primary product obtained in S1 was washed with anhydrous ethanol for 4 times, and then placed in a vacuum drying oven at 60° C. for 4 hours to remove the residual solvent (anhydrous ethanol) to obtain Co-Mg-Al-LDH.
[0051] Figure 1 Prepared in Example 1 [C 10 Phase diagram of mim][Ttfa] / H2O / TX-100 ionic liquid microemulsion. The figure shows [C 10 The microstructure of mim][Ttfa] / H2O / TX-100 microemulsion system can be divided into W / O, BC, and O / W.
[0052] Figure 2 This is the XPS graph of the petal-shaped Co-Mg-Al-LDH prepared in Example 1. The figure shows that the petal-shaped Co-Mg-Al-LDH nanomaterial is mainly composed of Co, Mg, Al, C, O, and H elements.
[0053] Figure 3 This is a SEM image of the petal-shaped Co-Mg-Al-LDH prepared in Example 1. The image shows that the prepared Co-Mg-Al-LDH nanomaterial has an obvious petal-shaped layered structure.
[0054] Figure 4 This is a N2 adsorption-desorption characterization diagram of the petal-shaped Co-Mg-Al-LDH prepared in Example 1. The figure shows that the prepared Co-Mg-Al-LDH nanomaterial is a mesoporous material formed by its flake stacking.
[0055] Figure 7 This is the N2 adsorption-desorption characterization diagram of Co-Mg-Al-LDH prepared in Comparative Example 1. The adsorption line and the desorption line do not overlap, indicating that mesopores exist in Co-Mg-Al-LDH.
[0056] Table 8 is a SEM image of the Co-Mg-Al-LDH prepared in Comparative Example 1, which shows that the Co-Mg-Al-LDH prepared in Comparative Example 1 has a layered structure.
[0057] Comparative Example 1: Agglomeration occurs when Co-Mg-Al-LDH is prepared by the conventional co-precipitation method because the prepared Co-Mg-Al-LDH has high surface energy: Since the surface energy of nanomaterials is relatively large, they are easy to aggregate together. Residual water molecules: After the hydrothermal reaction, a large number of water molecules will remain on the surface of the hydrotalcite (layered double hydroxide) nanocrystals. The huge surface tension of these water molecules will cause the hydrotalcite to agglomerate and form an agglomerate system of 1-2 μm. Inconsistent nucleation and growth: The co-precipitation method may result in uneven particle size because the precipitated particles are generated gradually with a large time difference, resulting in agglomeration.
[0058] The method for preparing petal-shaped Co-Mg-Al-LDH in Example 1 avoids agglomeration because the method can control the particle size and thickness: the method can effectively control the diameter and thickness of the particles by controlling the ratio of water and surfactant, thereby reducing agglomeration. Reduce surface energy: The preparation method in Example 1 provides a confined environment, reduces the surface energy of the nanoparticles, and reduces the agglomeration tendency caused by high surface energy. Avoid residual water molecules: In the preparation method in Example 1, the dual-responsive ionic liquid microemulsion system may reduce the residual water molecules on the surface of the nanocrystals, thereby reducing the agglomeration phenomenon caused by the surface tension of water molecules. Uniform nucleation environment: The preparation method in Example 1 provides a relatively uniform nucleation environment, which helps to reduce agglomeration caused by inconsistency between nucleation and growth. The dual-responsive ionic liquid microemulsion acts as a soft template, which enables the petal-shaped Co-Mg-Al-LDH material to play a directional role in the growth process.
[0059] Experiment 1: Effect of material dosage on the experiment
[0060] The initial concentration was 50 mg·L -1 Take 5 100 mL conical flasks and add 50 mL of 50 mg·L ciprofloxacin (CIP) solution into each conical flask. -1 After adding a magnetic bar to each conical flask, place it in the heating mantle of the magnetic stirrer, set the low-temperature thermostat temperature to 25°C, and start stirring.
[0061] First, add 0.05g of PMS to the CIP solution in each conical flask, and then react 0g, 0.005g, 0.0075g, 0.010g, and 0.020g of the petal-shaped Co-Mg-Al-LDH prepared in Example 1 respectively; take samples at 5min, 10min, 20min, 30min, 45min, and 60min, and filter the samples with a 0.22μm filter membrane. Then, use an ultraviolet spectrophotometer to measure the concentration of CIP in the solution, and set the wavelength to 272nm. Determine the spectrophotometric value of CIP, compare the value with the original solution, and calculate the degradation rate of CIP. The results are as follows: Figure 5 As shown in the figure, when the concentrations of CIP and PMS are constant, the concentration of Co-Mg-Al-LDH is 0.2 g·L -1 When , its degradation effect on CIP is optimal.
[0062] Experiment 2: Effect of PMS dosage on the experiment
[0063] The initial concentration was 50 mg·L -1 Take 4 100mL conical flasks and add 50mL of 50mg·L ciprofloxacin (CIP) solution into each conical flask. -1 After adding a magnetic bar to each conical flask, place it in the heating mantle of the magnetic stirrer, set the low-temperature thermostat temperature to 25°C, and start stirring.
[0064] 0.01g of Co-Mg-Al-LDH composite material was added to each conical flask, and then 0g, 0.0125g, 0.0250g, and 0.0500g of PMS were added to the solution for reaction. Samples were taken at 5min, 10min, 20min, 30min, 45min, and 60min, and the samples were filtered with a 0.22μm filter membrane. Then, an ultraviolet spectrophotometer was used for measurement, and the wavelength was set to 272nm. The spectrophotometric value of CIP was determined, and its value was compared with the original solution to calculate the CIP degradation rate. The results are shown in Figure 6 As shown in the figure, when the concentrations of Co-Mg-Al-LDH and CIP are constant and the concentration of PMS is 1.0 g·L -1 When , its degradation effect on CIP is optimal.
[0065] Example 2
[0066] This embodiment provides a method for preparing a petal-shaped Co-Mg-Al-LDH, which comprises the following steps:
[0067] S1, the mass ratio of polar phase water (H2O), [C 10mim][Btfa] and polyethylene glycol octylphenyl ether (TX-100) were mixed evenly to obtain a dual-responsive ionic liquid microemulsion;
[0068] The [C 10 mim][Btfa] is prepared as follows:
[0069] S101, first add N-methylimidazole and bromodecane in a molar ratio of 1:1 into a 250 mL round-bottom flask, then add ethyl acetate as a solvent and mix well, then reflux for 72 h at 80° C. under N2 protection to obtain a crude product; wash the crude product with ethyl acetate a 5 times, then evaporate the ethyl acetate a using a rotary evaporator at 60° C. for 30 min, then dry in a vacuum drying oven at 60° C. for 2 days to obtain an ionic liquid 1-decyl-3-methylimidazole bromide ([C 10 mim]Br); the volume ratio of the total amount of the ethyl acetate to the N-methylimidazole and the bromodecane is 1:2;
[0070] S102, dissolving the ionic liquid 1-decyl-3-methylimidazolium bromide obtained in S101 and ethanol in a volume ratio of 9:1 to obtain [C 10 mim]Br ethanol solution; the [C 10 mim]Br ethanol solution was added to the anion exchange column to perform Br - Exchange, get [C 10 mim]OH; the acid-base titration method was used to determine the [C 10 mim]OH ethanol solution [C 10 mim]OH concentration;
[0071] S103, the [C 10 mim]OH and benzoyltrifluoroacetone (Btfa) were mixed uniformly at a molar ratio of 1:1, reacted at room temperature (25°C) for 24 hours, and then evaporated by rotary evaporation at 60°C for 30 minutes to evaporate water to obtain a crude product b; the crude product b was placed in a vacuum drying oven and dried at 50°C for 2 days to obtain [C 10 mim][Btfa], the [C 10 mim][Btfa] has an anion of benzoyltrifluoroacetone and a cation of 1-decyl-3-methylimidazole;
[0072] S2. Firstly, cobalt nitrate hexahydrate is added to the dual-responsive ionic liquid microemulsion obtained in S1 to obtain a mixed solution; magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea are added to the mixed solution in sequence, and the mixture is stirred at room temperature (25° C.) for 0.5 h to obtain a mixture; the mixture is subjected to a hydrothermal reaction at a temperature of 140° C. for 24 h to obtain a primary product;
[0073] The concentration of cobalt element in the cobalt nitrate hexahydrate in the mixed solution is 0.6 mmol·mL -1 ; The molar ratio of the cobalt element in the cobalt nitrate hexahydrate, the magnesium element in the magnesium nitrate hexahydrate, the aluminum element in the aluminum nitrate nonahydrate and the urea is 1:50:16:291;
[0074] S3. The primary product obtained in S2 was washed with anhydrous ethanol three times, and then placed in a vacuum drying oven at 60° C. for 4 h to remove the residual solvent (anhydrous ethanol) to obtain a petal-shaped Co-Mg-Al-LDH.
[0075] The evaporation temperature in S101 of this embodiment can also be 50° C., 51° C., 52° C., 53° C.
[0076] ℃, 54℃, 56℃, 57℃, 58℃ or 59℃, and the time can also be 31min, 32min, 33min, 34min, 35min, 38min, 39min, 40min, 45min, 48min, 52min, 55min, 57min, 58min or 60min; the number of times the crude product is washed with ethyl acetate a can also be 3 times; the temperature of the evaporation in S103 and the evaporation in S104 can also be 50℃, 51℃, 52℃, 53℃, 54℃, 56℃, 57℃, 58℃
[0077] or 59° C., and the time may also be 31 min, 32 min, 33 min, 34 min, 35 min, 38 min, 39 min, 40 min, 45 min, 48 min, 52 min, 55 min, 57 min, 58 min or 60 min; the concentration of cobalt element in the cobalt nitrate hexahydrate in the mixed solution in S2 may also be 0.65 mmol·mL -1 ; The molar ratio of the cobalt element in the cobalt nitrate hexahydrate, the magnesium element in the magnesium nitrate hexahydrate, the aluminum element in the aluminum nitrate nonahydrate and the urea is 1:50:17:292.
[0079] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing petal-shaped Co-Mg-Al-LDH, characterized in that: The preparation method comprises the following steps: S1, mixing polar phase water, non-polar phase ionic liquid and surfactant uniformly to obtain a dual-responsive ionic liquid microemulsion; S2, first adding a cobalt source to the dual-responsive ionic liquid microemulsion obtained in S1 to obtain a mixed solution, and then sequentially adding a magnesium source, an aluminum source and a precipitant to the mixed solution to obtain a mixture; subjecting the mixture to a hydrothermal reaction to obtain a primary product; S3. The primary product obtained in S2 is washed and then dried to obtain a petal-shaped Co-Mg-Al-LDH.
2. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 1, characterized in that: The mass ratio of the polar phase water, the non-polar phase ionic liquid and the surfactant in S1 is 3.715:1.5:0.
75.
3. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 2, characterized in that: The surfactant is polyethylene glycol octylphenyl ether, and the non-polar phase ionic liquid is [C 10 mim][Ttfa]or[C 10 mim][Btfa].
4. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 3, characterized in that: The preparation method of the non-polar phase ionic liquid is: S101, firstly mixing N-methylimidazole and bromodecane, then adding ethyl acetate and mixing evenly, and then refluxing under N2 protection to obtain a crude product; washing the crude product with ethyl acetate a, then evaporating, and then drying to obtain an ionic liquid 1-decyl-3-methylimidazole bromide; S102, dissolving the ionic liquid 1-decyl-3-methylimidazolium bromide obtained in S101 in ethanol to obtain [C 10 mim]Br ethanol solution; the [C 10 mim]Br ethanol solution was added to an anion exchange column to obtain [C 10 mim]OH; S103, the [C 10 mim]OH and benzoyltrifluoroacetone were mixed evenly, reacted at room temperature for 24 hours, and then evaporated to obtain a crude product a; the crude product a was dried to obtain [C 10 mim][Btfa]; S104, the [C 10 mim]OH and 2-thenoyltrifluoroacetone were mixed evenly, reacted at room temperature for 24 hours, and then evaporated to obtain a crude product b; the crude product b was dried to obtain [C 10 mim][Ttfa].
5. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 4, characterized in that: The molar ratio of N-methylimidazole to bromodecane in S101 is 1:1, and the volume ratio of ethyl acetate to the total amount of N-methylimidazole and bromodecane is 1:2; the reflux temperature is 80°C and the time is 72h; the crude product is washed with ethyl acetate a 3-5 times; the evaporation temperature is 50-60°C and the time is 30-60min; the drying temperature is 60°C and the time is 2 days; the volume ratio of the ionic liquid 1-decyl-3-methylimidazole bromide to the ethanol in S102 is 9:
1.
6. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 4, characterized in that: S103 [C 10 mim]OH and the molar ratio of the benzoyltrifluoroacetone is 1:1, and the [C 10 mim]OH and the molar ratio of the 2-thenoyltrifluoroacetone is 1:1; the drying temperature in S103 and the drying temperature in S104 are both 50°C, and the time is both 2 days; the evaporation temperature in S103 and the evaporation temperature in S104 are both 50-60°C, and the time is both 30-60 min.
7. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 1, characterized in that: The cobalt source in S2 is cobalt nitrate hexahydrate, the magnesium source is magnesium nitrate hexahydrate, the aluminum source is aluminum nitrate nonahydrate, and the precipitant is urea; the molar ratio of the cobalt element in the cobalt source, the magnesium element in the magnesium source, the aluminum element in the aluminum source and the precipitant is 1:50:(16-17):(291-292); the concentration of the cobalt element in the cobalt source in the mixed solution is 0.6-0.7 mmol·mL -1 .
8. The method for preparing a petal-shaped Co-Mg-Al-LDH according to claim 7, characterized in that: The temperature of the hydrothermal reaction in S2 is 140° C. and the time is 24 h; the initial product in S3 is washed with anhydrous ethanol for 3-5 times, and the drying temperature is 60° C. and the time is 4 h.
9. A petal-shaped Co-Mg-Al-LDH, characterized in that: The petal-shaped Co-Mg-Al-LDH is prepared by the preparation method of any one of claims 1 to 8.
10. Use of the petal-shaped Co-Mg-Al-LDH as claimed in claim 9 for degrading ciprofloxacin in water.
Citation Information
Cited By
Modified diaphragm for lithium-sulfur battery and preparation method of modified diaphragm
CN121929749A